Global Loss Diversification in the Insurance Sector - Oleg Sheremet; André Lucas (Tinbergen Institute, 2008)
We study the possibility for international diversification of catastrophe risk by the insurance sector. Adopting the argument that large insurance losses may be a `globalizing factor' for the industry, we study the dependence of geographically distant insurance markets via equity returns. In particular, we employ conditional copula theory to model the bivariate dependence of the insurance industry. In contrast to earlier literature on this subject, we disentangle the causes of dependence stemming from the asset side from those from the liability side by conditioning on general market conditions. We find that for both Europe–America and Europe–Asia the dependence is significant. Moreover, we find asymmetric effects: the international dependence is particularly high for losses, even after conditioning for the asset side dependence. Finally, we investigate the time variation in copula parameters and find evidence that dependence in the insurance sector has increased over time, thus reducing the scope for international diversification of large losses in this sector.
Keywords: C32; C52; G15; 330; Catastrophic insurance losses; Copula and dependence; Diversification; Versicherungsschaden; Risikomodell; Katastrophe; Kopula (Mathematik); Welt